1999
DOI: 10.1001/jama.282.13.1290
|View full text |Cite
|
Sign up to set email alerts
|

Harassment of Lesbians as Medical Students and Physicians

Abstract: HOMOSEXUALITY REMAINS CONTROVERSIAL IN THIS COUNTRY. LAST YEAR'S brutal murder of Wyoming college student Matthew Shepard brought forth recognition that despite much greater acceptance of gay and lesbian people than in recent history, antihomosexual discrimination marked by occasional violence remains a divisive fixture in the American social landscape. 1 Certainly conditions for gay and lesbian people have improved, especially within the medical profession. A moderate number of gay and lesbian medical stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…36–38 In a survey conducted by the AAMC, 17% of LGB medical students described the social, personal, and learning environments at their institutions as hostile toward sexual minority students. 39 In a survey of LGB physicians, 15% reported experiencing harassment and 22% reported social ostracizing by professional colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…36–38 In a survey conducted by the AAMC, 17% of LGB medical students described the social, personal, and learning environments at their institutions as hostile toward sexual minority students. 39 In a survey of LGB physicians, 15% reported experiencing harassment and 22% reported social ostracizing by professional colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…12 The anonymity of our survey did not allow us to explore the experience of the small number of gay male and lesbian students. Much data on medical education have been collected in various countries such as Australia, [17][18][19] Canada, 20,21 the United States, 12,13,16,[22][23][24][25][26] and the United Kingdom. 27 It is generally felt that medical education with regard to attitudes toward and health issues of homosexuals has been inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies reported high rates of derogatory comments, substandard treatment, and disrespect toward LGBT patients and coworkers [19,20]. In another study, lesbian physicians were 4 times more likely than heterosexual female physicians to report experiencing harassment because of their sexual orientation, particularly during the training years [21]. Given these findings [19-21], it is not surprising that LGBT students consider the presence of identifiable supports, inclusive LGBT-curricula, and effective nondiscrimination policies before disclosing their orientation [15].…”
Section: Introductionmentioning
confidence: 99%